Information Transparency in Public Stock Offering Transactions in the Capital Market (Case Study of the Prospectus for the Initial Public Offering of PT Media Nusantara Cipta (PT MNC) Shares in 2007) - Tania Diah Anindhita (Journal Research of Social Science, Economics, and Management, 2023)
This article aims to analyze the role and responsibility of the state through the Financial Services Authority and the Indonesia Stock Exchange in monitoring misleading company prospectuses and legal remedies that can be taken by investors if they suffer losses due to misleading prospectuses. The method used in the research is juridical normative to analyze the application related to the legal position of the prospectus as a way to fulfill information disclosure, and to obtain a complete picture of information disclosure through a prospectus that must be supervised by the Financial Services Authority and the Indonesia Stock Exchange, where if misleading is found in the prospectus which at any time can cause losses, investment actors can take criminal, civil, and administrative sanctions, in addition to investment actors can also pursue dispute resolution through alternative institutions outside the court that have been accommodated by Indonesian positive law.